Optimization of Acid Degumming of Crude Rice Bran Oil (CRBO) on Phospholipid Removal Using Response Surface Methodology (RSM) - Damayanti, Astrilia; megawati, megawati; Winaningsih, Ima; Wicakso, Doni Rahmat; Nuryoto, Nuryoto; Rumbino, Yusuf; Prasetyo, Ridwan Anung; Rizki, Muhammad Prabu (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2025)
Rice bran, a byproduct of milling rice, has 60% nutritional content and potential for processing into higher-selling goods like rice bran oil (RBO). Degumming is the first stage of refining crude oil. This research aims to remove phospholipids in crude rice bran oil (CRBO) by optimizing acid degumming. Three variables were optimized in this study using Design Expert v13's response surface methodology (RSM) employing central composite design (CCD) experimental design: the amount of phosphoric acid (0.1, 0.15, and 0.2 %w/w), the degumming temperature (50, 70, and 90 C), and the degumming time (20, 30, 40 minutes). The experimental values and predicted results did not correlate well with percentages (%) of error, with more than 50% occurring in 4 of 19 runs. The model's p-value of 0.4939 ( 0.05) is non-significant, with the coefficient determination, R2 being 0.5026. Optimization with desirability value ( 0.5) results showed a phospholipid removal response of 40.479% under conditions of adding 0.1%w/w phosphoric acid, temperature of 83.21 C, and degumming time of 40 minutes, which were determined by Derringers methodology..